Francisco Niculoso Pisano’s Oeuvre: Iconographic Programs of His Ceramic Altarpieces - Prikladova, Mariia A. (Actual Problems of Theory and History of Art, 2024)
The paper is dedicated to study of the Spanish ceramic retablos of the 16th century, with a particular focus on the work of Francisco Niculoso Pisano. The author analyzes the iconographic program of the altars created by the Italian master, as well as the role of donators in their composition. The selected perspective of the study has determined the relevance and novelty of the subject matter presented. In his work, Francisco Niculoso successfully combines the principles of the Italian Renaissance with the Spanish tradition. As a true innovator in the art market of the Empire, he was one of the creators of Renaissance altarpieces in Seville, where an active role in the decorative design was given to grotesques. The artist was the first who introduced them to the city. The eclectic character of Francisco Niculoso’s altarpieces corresponds in its diversity to the artistic language of the emerging Spanish Empire. The paper analyzes the socio-cultural, historical, and religious contexts of the ceramic altarpieces created by Francisco Niculoso and reveals the features of his artistic manner.